The Right to Information (RTI): Legal Framework and Judicial Response in Nepal - Bhandari, Santosh (KDCBAR Law Journal, 2025)
The Right to Information (RTI) is a fundamental democratic tool that promotes transparency, accountability, and civic participation in governance. This study examines the global evolution of RTI, its implementation in Nepal, and the persistent challenges hindering its effectiveness. The purpose of this research is threefold: to analyze the historical and comparative development of RTI laws worldwide, to assess Nepal’s legal and institutional framework under the RTI Act (2007) and constitutional provisions, and to identify key implementation gaps and propose policy reforms. The methods and approach involve a qualitative analysis of legal documents, case laws, scholarly literature, and institutional reports, supplemented by comparative assessments with RTI regimes in different countries. Key measuring variables include legislative robustness, institutional compliance (e.g., response rates, proactive disclosures), bureaucratic resistance, public awareness levels, and digital infrastructure readiness. Findings reveal that while Nepal’s RTI framework aligns with global standards, its implementation suffers from bureaucratic inertia, political interference, weak enforcement by the National Information Commission (NIC), and a lack of public awareness—particularly in rural areas. Federalism has further complicated compliance due to uneven capacity across local governments. Suggestions for improvement include amending the RTI Act to clarify exemptions and enforcement mechanisms, strengthening the NIC’s quasi-judicial authority, expanding digital governance infrastructure, and launching nationwide awareness campaigns. The study reflects that without systemic reforms, Nepal’s RTI regime will remain an underutilized tool for democratic accountability.